Alterations of the Gut Microbiome Associated to Methane Metabolism in Mexican Children with Obesity - Sofía Magdalena Murga-Garrido; Yaneth Citlalli Orbe-Orihuela; Cinthya Estefhany Díaz-Benítez; Ana Cristina Castañeda-Márquez; Fernanda Cornejo-Granados; Adrian Ochoa-Leyva; Alejandro Sanchez-Flores; Miguel Cruz; Ana Isabel Burguete-García; Alfredo Lagunas-Martínez (MDPI AG, 2022)
Gut microbiota is associated with the development of metabolic disorders. To study its association with childhood obesity, we performed a cross-sectional study with 46 children (6-12 years old). We collected fecal samples, food-frequency questionnaires (FFQs), and anthropometric measurements. Shotgun metagenomics were used to obtain the microbial taxonomic diversity and metabolic potential. We identified two dietary profiles characterized by complex carbohydrates and proteins (pattern 1) and saturated fat and simple carbohydrates (pattern 2). We classified each participant into normal weight (NW) or overweight and obese (OWOB) using their body mass index (BMI) z-score. The ratio of Firmicutes/Bacteroidetes and alpha diversity were not different between the BMI groups. Genera contributing to beta diversity between NW and OWOB groups included Bacteroides rodentium, B. intestinalis, B. eggerthii, Methanobrevibacter smithii, Eubacterium sp., and Roseburia sp. B. rodentium was associated with lower BMI and dietary pattern 1 intake. Eubacterium sp. and Roseburia sp. were associated with BMI increments and high consumption of dietary pattern 2. Methane and energy metabolism were found enriched in under-represented KEGG pathways of NW group compared to OWOB. Complex dietary and microbiome interaction leads to metabolic differences during childhood, which should be elucidated to prevent metabolic diseases in adolescence and adulthood.